Memorable Food: Fighting Age-Related Neurodegeneration by Precision Nutrition - Milošević, Maja; Arsić, Aleksandra; Cvetković, Zorica; Vučić, Vesna (Frontiers in Nutrition, 2021)
The healthcare systems worldwide are seriously challenged by a raising prevalence of neurodegenerative diseases (NDD), which affect mostly, but not exclusively, the ever-growing population of elderly. The most known neurodegenerative diseases are Alzheimerʼs (AD), Parkinsonʼs and Huntingtonʼs disease, multiple sclerosis and amyotrophic lateral sclerosis, but some viral infections of the brain and traumatic brain injury may also cause NDD. Typical for NDD are malfunctioning of neurons and their irreversible loss, which often progress irreversibly to dementia and ultimately to death. Numerous factors are involved in pathogenesis of NDD: genetic variability, epigenetic changes, extent of oxidative/nitrosative stress, mitochondrial dysfunction, DNA damage. The complex interplay of all the above-mentioned factors may be a fingerprint of neurodegeneration, with different diseases being affected to different extents by particular factors. There is a voluminous body of evidence showing benefits of regular exercise to brain health and cognitive functions. Moreover, the importance of a healthy diet, balanced in macro- and micronutrients, in preventing neurodegeneration and slowing down a progression to full-blown disease is evident. Individuals affected by NDD almost inevitably have a low-grade inflammation and anomalies in lipid metabolism. Metabolic and lipid profile in NDD can be improved by Mediterranean diet. Many studies associated Mediterranean diet with a decreased risk of dementia and AD, but a cause-and-effect relation could not be deducted. Studies with caloric restriction showed neuroprotective effects in animal models, but the result in humans are inconsistent. The pathologies of NDD are complex and there is a great inter-individual (epi)genetic variance within any population. Furthermore, gut microbiome, being deeply involved in nutrient uptake and lipid metabolism, also represents a pillar of microbiome-gut-brain axis, and is linked with pathogenesis of NDD. Numerous studies on the role of different micronutrients (omega-3 fatty acids, bioactive polyphenols from fruit and medicinal plants) in prevention, prediction and treatment of NDD have been conducted, but we are still far away from the personalised diet plan for individual NDD patients. For this to come true, large-scale cohorts that would include precise monitoring of food intake, mapping of genetic variants, epigenetic data, microbiome studies, metabolome, lipidome and transcriptome data are needed.